Pop III i-process nucleosynthesis and the elemental abundances of SMSS J0313−6708 and the most iron-poor stars. (23rd November 2017) - Clarkson, O; Herwig, F; Pignatari, M
Abstract: We have investigated a highly energetic H-ingestion event during shell He burning leading to H-burning luminosities of log ( L H /L⊙ ) ∼ 13 in a 45 M⊙ Pop III massive stellar model. In order to track the nucleosynthesis which may occur in such an event, we run a series of single-zone nucleosynthesis models for typical conditions found in the stellar evolution model. Such nucleosynthesis conditions may lead to i -process neutron densities of up to ∼10 13  cm −3 . The resulting simulation abundance pattern, where Mg comes from He burning and Ca from the i process, agrees with the general observed pattern of the most iron-poor star currently known, SMSS J031300.36−670839.3. However, Na is also efficiently produced in these i -process conditions, and the prediction exceeds observations by ∼2.5 dex. While this probably rules out this model for SMSS J031300.36−670839.3, the typical i -process signature of combined He burning and i process of higher than solar [Na/Mg], [Mg/Al], and low [Ca/Mg] is reproducing abundance features of the two next most iron-poor stars HE 1017−5240 and HE 1327−2326 very well. The i process does not reach Fe which would have to come from a low level of additional enrichment. i process in hyper-metal-poor or Pop III massive stars may be able to explain certain abundance patterns observed in some of the most metal-poor CEMP-no stars.